Performance The Ethics and the Politics of Conservation and Care, Volume I - Hölling, Hanna B; Feldman, Jules Pelta; Magnin, Emilie (Routledge Advances in Theatre & Performance Studies, 2023)
This book focuses on performance and performance-based artworks as seen through the lens of conservation, which has long been overlooked in the larger theoretical debates about whether and how performance remains. Unraveling the complexities involved in the conservation of performance, Performance: The Ethics and the Politics of Conservation and Care (vol. 1) brings this new understanding to bear in examining performance as an object of study, experience, acquisition, and care. In so doing, it presents both theoretical frameworks and functional paradigms for thinking about-and enacting-the conservation of performance. Further, while the conservation of performance is undertheorized, performance is nevertheless increasingly entering the art market and the museum, meaning that there is an urgent need for discourse on how to care for these works long-term. In recent years, a few pioneering conservators, curators, and scholars have begun to create frameworks for the longterm care of performance. This volume presents, explicates, and contextualizes their work so that a larger discourse can commence. It will thus serve the needs of conservation students and professors, for whom literature on this subject is sorely needed. This interdisciplinary book thus implements a novel rethinking of performance that will challenge and revitalize its conception in many fields, such as art history, theater, performance studies, heritage studies, and anthropology.